ARSTANBEK IS THE GREAT MASTER OF THE ART OF SPEECH - Toktomatova G. O. (Vestnik Issyk-Kulʹskogo universiteta)
The article is about Arstanbek Buylash uulu, about his high creative power of personality, revealing his creative potential in the highest degree, about his creation of new, original, deep, incomparable works, about his discovery of those peaks, to which no one had reached before, about the fact that he was able to reach the pinnacle of mastery in the art of Aytysh, about the peculiarities of his sensual and tender inner world, mastery in reflecting the truth of life, his peculiarities of aesthetic perception in the ability to feel subtly, understanding and evaluation, his talent in choosing and finding the exact rhyming words and the ability to convey all this accompanied by komuz as a poet-improviser, also the manifestation of his feelings towards beauty in his works, about providing these people with aesthetic pleasure with komuz, the ability to express his thoughts and feelings accurately and clearly through different ways, his communicative ability, the ability to cooperate constructively with people, his ability to share the grief of others, kindness and many others. etc. Arstanbek is a great poet, thinker, leader-philosopher, clear-eyed as a saint, wise, virtuoso komuzist, singer, pouring like rain. His timeless works in the memory of the people with their humanity, critical reality remain in the hearts of people, souls, aesthetic consciousness and with special passion continue to live in the mouths of people.